EVALUASI NILAI KERUSAKAN JALAN PADA RUAS MOLINGKAPOTO SIMPANG KWANDANG MENGGUNAKAN SURFACE DISTRESS INDEX (SDI) DAN INTERNATIONAL ROUGHNESS INDEX (IRI) - Moh. Reza Jahja; Frice Lahmudin Desei; Yuliyanti Kadir (Composite Journal, 2026)
Road damage is a complex problem and can cause major losses for road users.The purpose of this study is to analyze the damage to the Molingkapoto road at the Kwandang intersection, and to examine the appropriate handling of the damage that occurs. The methods used in the study are the SDI and IRI methods. The SDI method is a visual assessment of damage conditions. In calculating the SDI value, 4 elements are used, namely % crack area, crack gap width, number of holes/100 m and depth of wheel ruts. The IRI method is the value of road surface flatness calculated from the cumulative number of ups and downs of the longitudinal profile surface divided by the distance/length of the measured surface. The IRI value in this study was taken per 100 m using the Roadlab Pro application. The results of the SDI method analysis showed good conditions of 82%, moderate 12%, minor damage 3%, and severe damage 3%. The road conditions were dominated by good conditions along 2.7 km. The results of the IRI method analysis showed very good conditions of 0%, good conditions of 68%, moderate 29%, bad 3%, and very bad 0%. The road conditions were dominated by good conditions along 4.5 km. The combination of SDI and IRI values showed that Molingkapoto road at the Kwandang intersection sta. 6+300 to sta. 9+600 was in moderate condition and only required routine maintenance.